A guide to useful CR/sustainability ‘How to embed CR’ guides - (:unkn) unknown (Cranfield University School of Management, 2009)
The guides reviewed provide advice or insight specifically into the discipline of CR – not general advice on business skills such as budgeting or line management. After collating the guides we wanted to include, we realised categorisation was needed to aid you when searching for a particular topic. Therefore, we use 11 themes for implementing and embedding CR: each one is a critical success factor for implementing CR but is also a stand-alone grouping of related activities: 1. Building CR into business purpose and strategy 2. Tone from the top 3. Governance and board oversight 4. Management processes 5. CR strategy incorporated into each business unit 6. Everybody’s business 7. Energising the value chain 8. Sustainability knowledge management 9. Trusted stewardship: effective communication and stakeholder engagement 10. Sustainability networks 11. The specialist CR/sustainability function